Genomic investigations of bacteriocins and bacteriophages in Streptococcus pneumoniae and other streptococci - Rezaei Javan, R (2019)
Streptococcus pneumoniae (the “pneumococcus”) is a major public health problem, leading to significant morbidity and mortality worldwide. The global increase in antimicrobial-resistant pneumococci is of serious concern, which necessitates investigations into novel antimicrobial strategies. Two promising areas of research are the exploitation of phages (viruses that infect bacteria) and bacteriocins (antimicrobial peptides produced by bacterial species to kill other bacteria). This thesis uses genomic approaches to address questions related to the prevalence, diversity and molecular epidemiology of bacteriocins and prophages (phage genomes that are integrated into bacterial chromosomes). The first part analysed >6,200 pneumococcal genomes and discovered 14 novel bacteriocin gene clusters. The molecular epidemiology of the bacteriocin clusters was investigated in the context of the pneumococcal population structure. The results revealed extraordinary bacteriocin diversity among pneumococci and the majority of bacteriocin clusters were also present in other streptococcal species. Genomic hotspots for the integration of different bacteriocin gene clusters were discovered. Bacteriocin genes were found to be transcriptionally active when the pneumococcus was under stress and when two different strains were co-cultured in broth. The second part describes the molecular epidemiology of satellite prophages (prophages that rely on the host and an additional helper phage for survival) in a large global and historical pneumococcal dataset. Forty-four unique satellite prophages were newly identified, which had persistent associations with specific widely-circulating pneumococcal clonal complexes over many decades. Collaborative experimental work demonstrated that one of these satellite prophages was associated with virulence in a murine model of infection. RNA sequencing revealed that satellite prophage genes were overexpressed when pneumococci were grown planktonically versus in in vitro biofilm experimental conditions. The final part analysed >1,300 genomes of 70 different Streptococcus species and identified nearly 800 prophages and satellite prophages. The data showed that prophages and satellite prophages were widely distributed among streptococci and constituted two distinct entities with little effective genetic exchange between them. Contrary to the current dogma that suggests prophages are bacterial species-specific, there was convincing evidence that transmission of prophages occurred between genetically different streptococcal species. These results broaden our understanding of bacteriocins and phages among streptococci and uncover many areas for future studies.